2021
DOI: 10.1038/s41396-021-00953-7
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient complexity triggers transitions between solitary and colonial growth in bacterial populations

Abstract: Microbial populations often experience fluctuations in nutrient complexity in their natural environment such as between high molecular weight polysaccharides and simple monosaccharides. However, it is unclear if cells can adopt growth behaviors that allow individuals to optimally respond to differences in nutrient complexity. Here, we directly control nutrient complexity and use quantitative single-cell analysis to study the growth dynamics of individuals within populations of the aquatic bacterium Caulobacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 48 publications
3
67
0
Order By: Relevance
“…For example, mucin derived oligosaccharide can inhibit virulence in P. aeruginosa (Wheeler et al, 2019), whereas free fucose cleaved from mucin increase virulence of E. coli (Pacheco et al, 2012). Also, motility can be regulated by cyanobacterial mucin and derived oligosaccharides (Reddi et al, 2018) or xylose in Caulobacter crescentus (D'Souza et al, 2021). However, there is still much to learn about the potential for oligosaccharides to act as control "knobs" of bacterial behavior.…”
Section: Challenge 3 | Sensing Regulation and Phenotypic Heterogeneitymentioning
confidence: 99%
“…For example, mucin derived oligosaccharide can inhibit virulence in P. aeruginosa (Wheeler et al, 2019), whereas free fucose cleaved from mucin increase virulence of E. coli (Pacheco et al, 2012). Also, motility can be regulated by cyanobacterial mucin and derived oligosaccharides (Reddi et al, 2018) or xylose in Caulobacter crescentus (D'Souza et al, 2021). However, there is still much to learn about the potential for oligosaccharides to act as control "knobs" of bacterial behavior.…”
Section: Challenge 3 | Sensing Regulation and Phenotypic Heterogeneitymentioning
confidence: 99%
“…Competition experiments revealed that spatial interactions can strongly affect the outcome of competition, oftentimes leading to the coexistence of multiple genotypes [ 43 , 120 , 125 ]. However, due to technical challenges and the transient nature of many primitive cell collectives [ 126 ], there is often a limited quantitative understanding of how genotypes exactly give rise to individual cell collectives and how these collectives subsequently grow and propagate in competition with other collectives. Since the spatiotemporal organization of collectives determines a genotype’s competitive success (i.e., rates of collective growth and reproduction)—making collectives the relevant unit of biological organization [ 49 , 50 ]—we need to understand how collective organization comes about to uncover how primitive forms of surface-associated multicellularity first arise and subsequent evolve.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, over the last decade, methods of empirical lineage tracking have strongly improved through advances in single-cell microscopy [126][127][128], image analysis [129], singlecell sequencing [51,130,131], and genome editing [132,133], thereby opening up the possibility of studying primitive cell collectives across a wide range of organisms [126]. For example, the stochastic and combinatorial expression of fluorescent proteins makes it possible to trace up to approximately 100 lineages without interrupting the spatial configuration of cells [134].…”
Section: Plos Biologymentioning
confidence: 99%
“…Diversity and quantity of nutrients might be two understudied factors that drive ecology and genome size evolution. A recent example shows that polysaccharide xylan triggers microcolonies, whereas monosaccharide xylose promotes solitary growth in Caulobacter (62). This is a striking example of how nutrient complexity can foster diverse niches for well-studied cells such as Caulobacter with genome size 4 Mb.…”
Section: Impact Of Ecosystem and Trophic Strategy On Genome Sizementioning
confidence: 99%